Type-D Personality and Elevated Psychological Symptoms In Early Adjustment of Severe Burn Injury Patients. (3rd April 2018) - Mujezinovic, Ajdin; Kwiet, Julia; Kornhaber, Rachel; Holt, Rachael; Streimer, Jeffrey; Vandervord, John; Rogers, Vanessa; Shaw, Joanne; Law, Jeremy; Cleary, Michelle; McLean, Loyola
ABSTRACT: Severe burn injuries are highly traumatic requiring lengthy recovery. High levels of distress in the early stages of treatment have been associated with poor physical and psychosocial recovery outcomes. Identifying traits relating to distress and personal coping styles may aid screening. Type-D, or 'distressed', personality may be such a trait. Type-D personality refers to an ongoing personality organization defined by a tendency to experience greater negative emotions and thoughts while simultaneously socially inhibiting their expression (Denollet et al., 1996 . Type-D has been linked to poor health outcomes in those with cardiovascular disease as well as other populations and has been found to be associated with elevated psychological symptoms. Currently, there are no investigations in the literature looking at Type-D in the severe burns injury population. This study aimed to investigate Type-D in severe burn injury patients, specifically regarding the presence of psychological symptoms in early treatment, using data gathered during a pilot study conducted at a severe burn injury unit. The DS-16, Davidson Trauma scale and Depression Anxiety and Stress Scale scores were analysed along with demographic and clinical data in 54 participants (40 males, 14 females). Participants who were found to have Type-D displayed significantly higher levels of psychopathology. Additionally, Type-D was found to be a significant predictor of psychological symptoms.